Co-trimoxazole induced Steven Johnson syndrome in HIV infected patient: things to consider - Kunti, Desak Putu Sukasanti Adi; Suryana, Ketut (International Journal of Research in Medical Sciences, 2024)
Co-trimoxazole is a sulfonamide fixed dose combination antibiotic which is effective and widely use in treatment and prevention of opportunistic infections in people living with HIV/AIDS, but can be potentially associated with adverse drug reactions including drug hypersensitivity reactions such as Steven Johnson syndrome. PLWHA individuals have up to a 1000-fold increased risk of drug hypersensitivity reaction compared to the general population, which is associated with drug exposure, immune dysregulation, and concurrent infections. Here we present a case report of a 59-year-old man with HIV who experienced Stevens-Johnson Syndrome after taking co-trimoxazole for 18 days. Therefore, we would like to remind you to be more careful when giving cotrimoxazole to PLWHA because it can take time for a hypersensitivity reaction to occur, also in a few cases, it can occur immediately.